2016
DOI: 10.1016/j.tsf.2016.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Optical, structural and electrical characterizations of stacked Hf-based and silicon nitride dielectrics

Abstract: International audienceHigh-k stacked dielectric structures were fabricated by a combination of RF magnetron sputtering and plasmaenhancedchemical vapor deposition. Their structural properties were studied versus deposition and annealingconditions by means of attenuated total reflection and high-resolution transmission electron microscopy techniques.All samples demonstrated smoothed surface (with a roughness below 1 nm) and abrupt interfaces betweenthe different stacked layers. No crystallization of Hf-based la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…GeHfO x layers were synthesized by MS, Ge‐ion implantation, EBE, and CVD . Annealing is usually performed between 600 and 900 °C .…”
Section: Influence Of Different Matrix Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…GeHfO x layers were synthesized by MS, Ge‐ion implantation, EBE, and CVD . Annealing is usually performed between 600 and 900 °C .…”
Section: Influence Of Different Matrix Materialsmentioning
confidence: 99%
“…The crystallization of the Ge proportion sets in between 600 and 800 °C . Pure HfO 2 layers crystallize between 700 and 800 °C . However, if Ge is incorporated into the HfO 2 , the crystallization temperature of the matrix is reduced significantly toward about 600 to 700 °C .…”
Section: Influence Of Different Matrix Materialsmentioning
confidence: 99%
“…A common rule of thumb 32,38,75 in the PE-CVD and PA-CVD work appears to be that lower R = NH 3 /SiH 4 flow ratios (R < 1) lead to Si-rich films (Si/N ratio > 1.1), while higher R (R > 1) produces N-rich films (N/Si ratio > 1.4), with inclusions of Si nanostructures or nanoscale intrusions at even higher R values. Also, lower substrate temperatures tend to yield a-SiN x :H films, with thermal annealing required to reduce H content and lead to film crystallization, while higher processing temperatures produce c-SiN x films with reduced hydrogen content.…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…Comparable results were obtained in the case of PE-CVD SiN x from a N 2 +SiH 4 mixture, with Si-rich films being formed at higher N 2 flows. 75 Studies of post-deposition thermal annealing effects were also reported under different annealing modes, gases, and durations, with 21 or without vacuum break between the deposition and annealing steps: 36,38,41,42 In the case of in situ annealing, 21 SiN x multilayered permeation barrier stacks deposited on PET substrates <100…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
See 1 more Smart Citation